EVALUATION OF ACCIDENTS WITH DOMINO EFFECT IN LPG STORAGE AREAS - Alencar, J. R. B.; Barbosa, R. A. P.; de Souza Jr., M. B. (Revista de Engenharia Térmica, 2005)
The term domino effect denotes a chain of accidents, or situations, in which a fire/explosion load generated by an accident in one unit in an industry causes secondary and higher order accidents in other units. Such chains of accidents have a greater propensity to cause damage than stand-alone accidents. Most of the past risk assessment studies deal with accident in a single industry, more so in one of the units of an industry. But, often, accident in one unit causes a secondary accident in a nearby unit, which in turn may trigger a tertiary accident, and so on. The probability of occurrence and adverse impacts of such domino or cascading effects are increasing due to increasing congestion in industrial complexes and increasing density of human population around such complexes. Accidents with domino effect are seldom studied. LPG storage areas could produce the worst possible consequences in the event of an unforeseen incident. This work illustrates the application of models to evaluate the impacts of events with fire and explosion in LPG tanks on other similar units in the park and the possibility of occurrence of a domino effect. The criteria for occurrence of accidents with domino effect adopted in this work were 37.5 kW/m2 in case of fire radiation and an overpressure of 0.7 atm in explosion cases in a receptor body. The spacing between LPG tanks was evaluated. The results show that such spacing is minimal and does not represent, as it should, a parameter indicating a safe distance able to prevent the propagation of an accident with domino effect.